Kualitas Fisik dan Kandungan Protein Kasar Silase Kulit Buah Kakao Berbeda Klon Sebagai Pakan Ternak - Fitriawaty, F; H, Rahmi; Nurhafsah, N; Andriani, Ida; Fitrahtunnisa, F (Journal Galung Tropika, 2020)
This study aims to determine the physical quality and crude protein content of cocoa pod husk silage (CBC) from different clones. The pods used came from six clones, namely Sulawesi1 (S1), Sulawesi2 (S2), Local 01 (L01), local 02 (L02), local Padantana (LP), and a mixture of all clones (S1+S2+L01+L02+LP), which is referred to as mixed silage. The study used a completely randomized design (CRD) with silage treatment of cocoa pod husks for each clone with 30% rice bran added. Meanwhile, the bran was not added to mixed silage. The data were analyzed using the analysis of variance test (ANOVA), and the Duncan test followed the difference between treatments. The results showed that the silage of all clone treatments had good physical quality with a distinctive sour fermentation aroma and a color that did not differ much from the original color of each clone's cocoa pods. There are differences in crude protein content of mixed cocoa pod husk silage and between clones. The highest crude protein content was found in mixed silage, namely 6.02%, and the lowest in local clones 02, namely 4.80%.